Economic Nationalism in Small EU Member States : Implications for the Internal Market and Fiscal Cohesion (2010–2025) - Khirsina, Mariia (2025)
This thesis examines how economic nationalism in three small EU member states Malta, Czechia, and Luxembourg – influences internal-market and fiscal cohesion between 2010 and 2025 in the European Union. The study analyses how external shocks activate nationally oriented subsidy policies and how these, in turn, interact with EU-level cohesion mechanisms. Theories of post-functionalism, differentiated integration, and fiscal-integration are applied for the interpretation of results. The empirical methodology combines a comparative case-study approach with fixed-effects panel regression models. The findings show that economic nationalism does not uniformly weaken EU integration. From hypothesis testing, it is found that rising national subsidy intensity does not weaken internal-market cohesion: intra-EU trade remains stable even when domestic subsidies increase. On the other hand, governance capacity is a key factor in shaping fiscal-cohesion outcomes: countries with stronger administrative systems, particularly Luxembourg, achieve consistently higher EU fund-absorption rates. The econometric results further reveal a negative and statistically significant relationship between subsidy intensity and EU-fund absorption – this indicates a moderate crowding-out effect. It is shown that economic nationalism becomes consequential for cohesion only when domestic fiscal expansion competes with limited administrative and/or institutional capacity. This study contributes an original insight: in small states, it is the administrative strength that determines whether national subsidy programs strengthen or diminish EU’s market and fiscal cohesion.